Fourier-based periodicity analysis and lightweight RC calibration for heating load modeling under limited sensing - Seon-In Kim; Deuk-Woo Kim; Eui-Jong Kim (Energy and Buildings, 2026)

Digital-twin tool for a drinking water distribution system using augmented reality and EPANET - Ji-Ye Park; Kwang-Ju Kim; Minhyuk Jeung; In-Su Jang; Jung-Won Yu; Mi-Seon Kang; Hyun-Su Bae; Changyoon Jeong; Sang-Soo Baek (Environmental Modelling & Software, 2026)

Effects of eco-friendly REDOX water treatment on growth and antioxidant activity in lettuce and kale - Min Hyeok Baek; In Seon Kim; Jung Su Jo (Horticulture, Environment, and Biotechnology, 2026)

Characterization and comparative analysis of saponins in various spinach (Spinacia oleracea L.) cultivars according to growing seasons - Su-Yeon Lee; Doo-Young Kim; Hyun-Jae Jang; Seon Min Oh; Hyoung-Geun Kim; Jongmin Ahn; In-Seo Heo; Heung Joo Yuk; Eun Kyoung Seo; Sei-Ryang Oh; Hyung Won Ryu (Food Chemistry, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

A Dual-Modality nanozyme Exploiting ROS-Responsive oxygen Catalysis for Precision NF-κB pathway Suppression in gouty arthritis - Sathiyamoorthy Padmanaban; Sree Samanvitha Kuppa; Omkar Sangabathula; Amal Babu; Adityanarayan Mohapatra; Sung Sun Kim; Hong Yeol Yang; Aravindkumar Sundaram; Hyung Keun Kim; Jong Keun Seon; In-Kyu Park (Chemical Engineering Journal, 2025)

Enhancement of renal fibrosis in PHF20 transgenic mice - Uijin Juang; Soohyeon Lee; Suhwan Gwon; Woohyeong Jung; Huonggiang Nguyen; Qingzhi Huang; Beomwoo Lee; So Hee Kwon; Seon-Hwan Kim; In Soo Kim; Jongsun Park (Toxicological Research, 2025)

Tribuli Fructus alleviates 1-methyl-4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease by suppressing neuroinflammation via JNK signaling - Jin Hee Kim; Eugene Huh; Hyeyoon Eo; Jin Se Kim; Youngji Kwon; In Gyoung Ju; Yujin Choi; Hae-Jee Yoon; So-Ri Son; Dae Sik Jang; Seon-Pyo Hong; Hi-Joon Park; et al. (Metabolic Brain Disease, 2024)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

3-Methylcatechol mediates anti-fecundity effect by inhibiting estrogen-related receptor-induced glycolytic gene expression in Myzus persicae - Woo-Ram Park; Hueng-Sik Choi; Jae-Hak Moon; In-Seon Kim; Don-Kyu Kim (Pesticide Biochemistry and Physiology, 2024)

Cold tolerance in Campylobacter jejuni and its impact on food safety - Jeong In Hur; Jinshil Kim; Mi Seon Kang; Hyun Jung Kim; Sangryeol Ryu; Byeonghwa Jeon (Food Research International, 2024)

S100A8/A9-RAGE pathway and chronic airway inflammation in smoke-induced lung carcinogenesis - Sung Bae Cho; In Kyoung Kim; Hye Seon Kang; Sang Haak Lee; Chang Dong Yeo (Molecular & Cellular Toxicology, 2024)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Asian-specific 3’UTR variant in CDKN2B associated with risk of pituitary adenoma - Byeong Ju Youn; Hyun Sub Cheong; Suhg Namgoong; Lyoung Hyo Kim; In Ki Baek; Jeong-Hyun Kim; Seon-Jin Yoon; Eui Hyun Kim; Se Hoon Kim; Jong Hee Chang; Sun Ho Kim; Hyoung Doo Shin (Molecular Biology Reports, 2022)

Normobaric hyperoxia re-sensitizes paclitaxel-resistant lung cancer cells - Jeonghyeon Im; Hee Young Kwon; In Kyoung Kim; Chang Dong Yeo; Sei Won Kim; Heayon Lee; Hye Seon Kang; Sang Haak Lee (Molecular & Cellular Toxicology, 2022)

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Tissue-specific DNA damage response in Mouse Whole-body irradiation - Seon-Gyeong Lee; Namwoo Kim; In Bae Park; Jun Hong Park; Kyungjae Myung (Molecular & Cellular Toxicology, 2022)
Background Genomic instability is a hallmark of various cancers, and DNA repair is an essential process for maintaining genomic integrity. Mammalian cells have developed various DNA repair mechanisms in response to DNA damage. Compared to the cellular response to DNA damage, the in vivo DNA damage response (DDR) of specific tissues has not been studied extensively. Objective In this study, mice were exposed to whole-body gamma (γ)-irradiation to evaluate the specific DDR of various tissues. We treated male C57BL6/J mice with γ-irradiation at different doses, and the DDR protein levels in different tissues were analyzed. Results The level of gamma-H2A histone family member X (γH2AX) increased in most organs after exposure to γ-irradiation. In particular, the liver, lung, and kidney tissues showed higher γH2AX induction upon DNA damage, compared to that in the brain, muscle, and testis tissues. RAD51 was highly expressed in the testis, irrespective of irradiation. The levels of proliferating cell nuclear antigen (PCNA) and ubiquitinated PCNA increased in lung tissues upon irradiation, suggesting that the post-replication repair may mainly operate in the lungs in response to γ-irradiation. Conclusion These results suggest that each tissue has a preferable repair mechanism in response to γ-irradiation. Therefore, the understanding and application of tissue-specific DNA damage responses could improve the clinical approach of radiotherapy for treating specific cancers.

Mortality and Physiological Responses with Regard to the Surf Clam, Mactra quadrangularis, Exposed to Chlorine - Seon-Sik Lee; Hyung-Jin Ahn; In-Uk Hwang; Eun Kim; Kyung-Nam Han (Ocean Science Journal, 2021)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Retained or altered expression of major histocompatibility complex class I in patient-derived xenograft models in breast cancer - In Hye Song; Young-Ae Kim; Hyeonjin Lee; Hye Seon Park; In Ah Park; Chan Kyu Sim; Myeong Sup Lee; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2019)

Isolation of putative pepper defense-related genes against the pathogen Phytophthora capsici using suppression subtractive hybridization/macroarray and RNA-sequencing analyses - Dong-Hwan Kim; Won-Hee Kang; Seon-In Yeom; Byung-Dong Kim (Horticulture, Environment, and Biotechnology, 2019)

Identification of Optimal Concentration of Silicon Application and Its Roles in Uptake of Essential Nutrients in Soybean (Glycine max L.) - Yeon-Gyeong Park; Seon-Min Park; Chae-In Na; Yoonha Kim (Journal of Crop Science and Biotechnology, 2019)

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes - Hyo-In Choi; Jung Ae Hong; Min-Seok Kim; Sang Eun Lee; Sung-Ho Jung; Pil Whan Yoon; Joon Seon Song; Jae-Joong Kim (Cardiovascular Toxicology, 2019)

Identification of endogenous microRNA references in porcine serum for quantitative real-time PCR normalization - In-Seon Bae; Kang-Seok Seo; Sang Hoon Kim (Molecular Biology Reports, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Practice Patterns in Distinguishing Between Background Pain and Breakthrough Pain During Patient Education: a Korean Physician Survey - Jinyoung Shin; Do Yeun Kim; Juneyoung Lee; Youn Seon Choi; In Gyu Hwang; Sun Kyung Baek; Min Seok Seo; Jae Yong Shim (Journal of Cancer Education, 2018)

LED light for in vitro and ex vitro efficient growth of economically important highbush blueberry (Vaccinium corymbosum L.) - Cao Dinh Hung; Chang-Hee Hong; Seon-Ki Kim; Kyu-Han Lee; Jea-Young Park; Min-Woo Nam; Dae-Ho Choi; Hye-In Lee (Acta Physiologiae Plantarum, 2016)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Effects of phenotypic and RAPD variations on ecophysiological characterization of reeds (Phragmites australis) in Suncheon Bay - In Seon Jeon; Da Som Kwon; Hoon Shin; Won Bok Kim; Na Roo Kang; Sun Mi Whang; Mi Sun Kim; Soo Jin Wi; Ky Young Park (Journal of Plant Biology, 2015)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Melatonin improves adriamycin-induced hepatic oxidative damage in rats - In-Chul Lee; Sung-Hwan Kim; Hyung-Seon Baek; Changjong Moon; Chun-Sik Bae; Sung-Ho Kim; Won-Kee Yun; Ki-Hoan Nam; Hyoung-Chin Kim; Jong-Choon Kim (Molecular & Cellular Toxicology, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

Melatonin attenuates gentamicin-induced nephrotoxicity and oxidative stress in rats - In-Chul Lee; Sung-Hwan Kim; Sang-Min Lee; Hyung-Seon Baek; Changjong Moon; Sung-Ho Kim; Seung-Chun Park; Hyoung-Chin Kim; Jong-Choon Kim (Archives of Toxicology, 2012)

Pycnogenol® prevents hexavalent chromium-induced spermatotoxicity in rats - Sung-Hwan Kim; In-Chul Lee; Hyung-Seon Baek; Changjong Moon; Seong-Soo Kang; Chun-Sik Bae; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Isolation of an Rx homolog from C. annuum and the evolution of Rx genes in the Solanaceae family - Jinxia Shi; Seon-In Yeom; Won-Hee Kang; Min-Kyu Park; Doil Choi; Jin-Kyung Kwon; Jung-Heon Han; Heung-Ryul Lee; Byung-Dong Kim; Byoung-Cheorl Kang (Plant Biotechnology Reports, 2011)

A grid-based rainfall-runoff model for flood simulation including paddy fields - In-Kyun Jung; Jong-Yoon Park; Geun-Ae Park; Mi-Seon Lee; Seong-Joon Kim (Paddy and Water Environment, 2011)

2-Aminobenzoic acid of Bacillus sp. BS107 as an ISR determinant against Pectobacterium carotovorum subsp. carotovotrum SCC1 in tobacco - Si Young Yang; Myung Ryeol Park; In Seon Kim; Young Cheol Kim; Jung Wook Yang; Choong-Min Ryu (European Journal of Plant Pathology, 2011)

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6 - Jang Hoon Lee; Kyung Cheol Ma; Sug Ju Ko; Beom Ryong Kang; In Seon Kim; Young Cheol Kim (Current Microbiology, 2011)

Characterization of chemical properties of atmospheric aerosols over Anmyeon (South Korea), a super site under Global Atmosphere Watch - Sung-Hwa Park; A. S. Panicker; Dong-In Lee; Woon-Seon Jung; Sang-Min Jang; Min Jang; Dongchul Kim; Yu-Won Kim; Harrison Jeong (Journal of Atmospheric Chemistry, 2010)

Inhibitory effect of immature plum on PMA-induced MMP-9 expression in human hepatocellular carcinoma - Mi Hee Yu; Hyo Gwon Im; Sung Gyu Lee; Dae-Ik Kim; Hwa Jeong Seo; In-Seon Lee (Natural Product Research, 2009)

Effects of ethanol extract from Saururus chinensis (Bour.) Baill on lipid and antioxidant metabolisms in rats fed a high-fat diet - Mi Hee Yu; Hyo Gwon Im; Ji-Won Lee; Mi-Hyang Hwang Bo; Hyun-Jeong Kim; Suk Kyung Kim; Shin Kyo Chung; In-Seon Lee (Natural Product Research, 2008)

Molecular authentication of ginseng cultivars by comparison of internal transcribed spacer and 5.8S rDNA sequences - Ok Tae Kim; Kyong Hwan Bang; Dong Su In; Jei Wan Lee; Young Chang Kim; Yoo Soo Shin; Dong Yun Hyun; Sung Sik Lee; Seon Woo Cha; Nak Sul Seong (Plant Biotechnology Reports, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Reproducibility of Quantitative Estimate of Magnetocardiographic Ventricular Depolarization and Repolarization Parameters in Healthy Subjects and Patients with Coronary Artery Disease - Hyun Kyoon Lim; Namsik Chung; Kiwoong Kim; Young-Guk Ko; Hyukchan Kwon; Yong-Ho Lee; Jin-Bae Kim; Jung Rae Cho; Jin-Mok Kim; In-Seon Kim; Yong Ki Park (Annals of Biomedical Engineering, 2006)

Optimization of direct somatic embryogenesis from mature zygotic embryos ofPanax ginseng C. A. Meyer - Ok Tae Kim; Tae Soo Kim; Dong Soo In; Kyong Hwan Bang; Young Chang Kim; Yong Eui Choi; Seon Woo Cha; Nak Sul Seong (Journal of Plant Biology, 2006)

Temperature-dependent index of mitotic interval τ0 in greenling Hexagrammos otakii - In-Seok PARK; Eun-Mi KIM; Seon Rang WOO; Sung-Yong OH; Dong Soo KIM; Jun Wook HUR (Fisheries Science, 2006)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)

EFFECTS OF ULMUS DAVIDIANA PLANCH ON MINERALIZATION, BONE MORPHOGENETIC PROTEIN-2, ALKALINE PHOSPHATASE, TYPE I COLLAGEN, AND COLLAGENASE-1 IN BONE CELLS - SUNG-KOO KANG; KAP-SUNG KIM; YU-SEOK BYUN; SEOK-JONG SUH; UN-HO JIM; KYUNG-HO KIM; IN-SEON LEE; CHEORL-HO KIM (In Vitro Cellular & Developmental Biology - Animal, 2006)

IMMUNOSUPPRESSIVE ACTIVITY OF DEER ANTLER EXTRACTS OF CERVUS KOREAN TEMMINCK VAR. MANTCHURICUS SWINHOE, ON TYPE II COLLAGEN-INDUCED ARTHRITIS - SUNG-KOO KANG; KAP-SUNG KIM; SUNG-IL KIM; KANG-HYUN CHUNG; IN-SEON LEE; CHEORL-HO KIM (In Vitro Cellular & Developmental Biology - Animal, 2006)

Genotyping Possible Polymorphic Variants of Human Mismatch Repair Genes in Healthy Korean Individuals and Sporadic Colorectal Cancer Patients - Jin C. Kim; Seon A. Roh; Kum H. Koo; In H. Ka; Hee C. Kim; Chang S. Yu; Kang H. Lee; Jung S. Kim; Han I. Lee; Walter F. Bodmer (Familial Cancer, 2004)

Environmental fate of the triazole fungicide propiconazole in a rice-paddy-soil lysimeter - In Seon Kim; Lee A. Beaudette; Jae Han Shim; Jack T Trevors; Yong Tack Suh (Plant and Soil, 2002)

Fractional precipitation for paclitaxel pre-purification from plant cell cultures of Taxus chinensis - Jin-Hyun Kim; In-Seon Kang; Hyung-Kyoon Choi; Seung-Suh Hong; Hyun-Soo Lee (Biotechnology Letters, 2000)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)